Optical Frequency Comb Generation based on Erbium Fiber Lasers - Droste, Stefan; Ycas, Gabriel; Washburn, Brian R.; Coddington, Ian; Newbury, Nathan R. (My University, 2016)
Optical frequency combs have revolutionized optical frequency metrology and are being actively investigated in a number of applications outside of pure optical frequency metrology. For reasons of cost, robustness, performance, and flexibility, the erbium fiber laser frequency comb has emerged as the most commonly used frequency comb system and many different designs of erbium fiber frequency combs have been demonstrated. We review the different approaches taken in the design of erbium fiber frequency combs, including the major building blocks of the underlying mode-locked laser, amplifier, supercontinuum generation and actuators for stabilization of the frequency comb.